Imigração Libanesa para Irati-PR: história e comunidade. - Godoi, Adriano Pinto (2018)
The municipality of Irati - PR was established with the contribution of several ethnic groups. Among the immigrants who arrived, the most prominent are the Poles and Ukrainians, whose make up the majority. However, this dissertation discusses about the Lebanese immigration to Irati. It portrays the arrival of the Lebanese immigrants to Brazil and later to Irati. It points out their mishaps and confrontations until they settle in this municipality. It reveals how and when they arrived; where they went to work; their beliefs (religion) and customs. It also addresses their traditions and struggles to maintain their roots. This work also shows stories of lives and some important personages, whose participated directly in the historical construction of the municipality. The facts that marked the Lebanese immigration and its implications are discussed in this dissertation, the discriminations and wars are part of the context, as well as their search for life improvement, a factor directly linked to the concepts of immigration.